2021
DOI: 10.1101/2021.03.26.437230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding Object Weight from Electromyography during Human Grasping

Abstract: Human urges, desires, and intentions manifest themselves in voluntary action. The final stages of such voluntary action are the muscle contractions that bring it about. Electromyography (EMG) signals measure such muscle contractions. Decoding action contents from EMG require advanced methods for detection, decomposition, processing, and classification and remains a challenge in neuroscience. This study presents a new, time-domain method of classifying EMG for grasping different types of objects. Our proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Specifically, the anterior deltoid and brachioradialis support reaching and lifting movements, whereas the common extensor digitorum, first dorsal interosseous, and the flexor digitorum profundus contribute mainly to the precision grip (Kapandji, 1980;Maier and Hepp-Reymond, 1995;Bonnefoy et al, 2009). Additionally, the target muscles have been identified to be informative as an indirect measure of grip force (Hoozemans and Van Dieen, 2005;Lashgari et al, 2021). The EMG data were used only in the multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the anterior deltoid and brachioradialis support reaching and lifting movements, whereas the common extensor digitorum, first dorsal interosseous, and the flexor digitorum profundus contribute mainly to the precision grip (Kapandji, 1980;Maier and Hepp-Reymond, 1995;Bonnefoy et al, 2009). Additionally, the target muscles have been identified to be informative as an indirect measure of grip force (Hoozemans and Van Dieen, 2005;Lashgari et al, 2021). The EMG data were used only in the multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, it strongly enhances the scientific armamentarium used to investigate volition [3,4]. And, more specifically, decoding intention in real time would open the door to interesting experimental possibilities, such as interventions to facilitate or frustrate intentions [5][6][7], and intention-contingent stimulation [3]. Technological advances of recent decadessuch as untethered, wireless recording, machinelearning-based analysis, and real-time analysis of raw electroencephalography (EEG) signal have increased the interest in EEG based BCI approaches [8].…”
Section: Introductionmentioning
confidence: 98%
“…These studies have suggested that successful classification and pattern recognition of EMG signals require three main steps in the following order: (i) data preprocessing, (ii) feature extraction, and (iii) classification. Common EMG data preprcoessing steps include low- and high-pass filtering, whereas feature extraction is a method of finding intrinsic and meaningful information that may be latent in the EMG signal [ 12 , 13 ]. Over the past few decades, various manual EMG feature-extraction methods have explored in the time and/or frequency domains [ 14 ].…”
Section: Introductionmentioning
confidence: 99%